2018
DOI: 10.1063/1.5044864
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pressure-driven assembly of polymer coated nanoparticles

Abstract: Abstract. High-pressure experiments have successfully produced a variety of gold nanostructures by compressing polymer coated spherical nanoparticles. We apply atomistic simulation to understand the role of the soft polymer response in determining the pressure-driven assembly of gold nanostructures. Quasi-isentropic experiments have shown that 1D, 2D and 3D nanostructures can be formed and recovered from dynamic compression of fcc superlattices of alkanethiol-coated gold nanocrystals on Sandia's Veloce pulsed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Lane et al suggested that the binding energy of S–Au is also critical. They found that the degree of sintering was significantly affected by the change of the S–Au binding energy . Lowering the binding energy seems to indicate that NP–NP sintering threshold pressures could be reduced.…”
Section: Pressure Induced Np Mesoscale Structure Phase Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lane et al suggested that the binding energy of S–Au is also critical. They found that the degree of sintering was significantly affected by the change of the S–Au binding energy . Lowering the binding energy seems to indicate that NP–NP sintering threshold pressures could be reduced.…”
Section: Pressure Induced Np Mesoscale Structure Phase Transformationmentioning
confidence: 99%
“…They found that the degree of sintering was significantly affected by the change of the S−Au binding energy. 216 Lowering the binding energy seems to indicate that NP−NP sintering threshold pressures could be reduced. This seems consistent with experimental results.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Recent experiments and simulations have demonstrated the possibility of transforming 3D NPSLs into functional low-dimensional nanostructures, such as nanowires and nanosheets, by subjecting them to a large external stress, both in quasi-static loading and superfast dynamic compression. , The mechanics of such transformations, however, is not entirely established. For example, it has been suggested that the quasi-static transformation of NPSLs into nanowires occurs as a result of a combination of applied hydrostatic pressure and deviatoric stress on the superlattice. ,, Furthermore, it is desirable to decrease the operating hydrostatic pressures and deviatoric stresses to make the fabrication process more scalable.…”
Section: Introductionmentioning
confidence: 99%
“…Snapshots showing the contact region between neighboring gold NPs at uncompressed condition (A) and after dynamic compression with ligand-gold binding energies of 9.2 kcal/mol (B) and 2.18 kcal/mol (C), respectively. Adapted with permission from ref . Copyright 2018 AIP Publishing.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…NP surfaces are usually passivated by an organic monolayer of alkane chain ligands to prevent aggregation. Lane et al examined the role of the binding energy between organic ligands and a gold core using MD simulations. They selected two Au-S binding energies of 9.2 kcal/mol from Luedtke and Landman and 2.18 kcal/mol from Henz et al and found that with the lower binding energy, the degree of sintering, i.e., the direct Au-Au contact area, increases significantly (Figures A–C).…”
Section: Molecular Modelingmentioning
confidence: 99%